GAMBARAN FAKTOR RISIKO PENYAKIT JANTUNG KORONER DI RSUD ARIFIN ACMAD PEKANBARU - Jamin " "; Safri " "; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract   This research aims to invensticate the description of the risk factors in patients with coronary heart disease. Research method was descriptive research with cross sectional approach. This study was conducted in inpatient flamboyant Arifin Achmad Pekanbaru who diagnosed with coronary heart disease. The number of respondent were which selected using pusposive sampling. Instrument used was a questionnaire that was tested validity and reliability. Data analysis used for this research was univariate. The results showed that the average age of coronary heart disease 53 years, female sex 53.3% of coronary heart disease, followed by 63.3% had diabetes, hypercholesterolemia had 73.3%, 76.7% smoked and 50% obesity. Based on the results of this study, it is suggested that keep healthy behavior with healthy food and cholesterol impartial and regular exercise are important factors in the prevention of coronary heart disease.